2018
DOI: 10.1073/pnas.1810701115
|View full text |Cite
|
Sign up to set email alerts
|

Photoreceptive retinal ganglion cells control the information rate of the optic nerve

Abstract: SignificanceNoise in the visual signal falls as ambient light increases, allowing the retina to extract more information from the scene. We show here that a measure of ambient light produced by the small number of inner retinal photoreceptors [intrinsically photosensitive retinal ganglion cells (ipRGCs)] regulates intrinsic rates of spike firing across the population of retinal ganglion cells that form the optic nerve. Increased firing at higher irradiance allows the ganglion cells to convey more information. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 40 publications
(67 reference statements)
0
52
0
1
Order By: Relevance
“…While ipRGCs were first appreciated for their roles in subconscious visual behaviors, a growing body of evidence has demonstrated that ipRGCs also make an important contribution to image‐forming vision (Allen et al, ; Allen, Storchi, Martial, Bedford, & Lucas, ; Barnard, Hattar, Hankins, & Lucas, ; Estevez et al, ; Milosavljevic et al, ; Schmidt et al, ; Storchi et al, ; Storchi et al, ; Zele, Adhikari, Cao, & Feigl, ). M4 and M5 ipRGCs have emerged as important ipRGC subtypes that participate in the image‐forming pathway, but it is still unclear how to definitively distinguish between these subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…While ipRGCs were first appreciated for their roles in subconscious visual behaviors, a growing body of evidence has demonstrated that ipRGCs also make an important contribution to image‐forming vision (Allen et al, ; Allen, Storchi, Martial, Bedford, & Lucas, ; Barnard, Hattar, Hankins, & Lucas, ; Estevez et al, ; Milosavljevic et al, ; Schmidt et al, ; Storchi et al, ; Storchi et al, ; Zele, Adhikari, Cao, & Feigl, ). M4 and M5 ipRGCs have emerged as important ipRGC subtypes that participate in the image‐forming pathway, but it is still unclear how to definitively distinguish between these subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Given the capacity of at least some ipRGCs to act as irradiance detectors (Dacey et al, 2005;Wong et al, 2005;Schmidt and Kofuji, 2009;Davis et al, 2015;Storchi et al, 2015), their intra-retinal connectivity has been considered as a mechanism for adjusting retinal function according to ambient light levels. Accordingly, there is evidence of ipRGC influences over visual response characteristics in both mice and humans (Hankins and Lucas, 2002;Allen et al, 2014;Allen and Lucas, 2016;Milosavljevic et al, 2018;Allen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have suggested numerous mechanisms that influence the paths taken by cells in early mammalian embryos. On page 404, Lim et al 1 describe a surprising role for a protein polymer, keratin, in the first of these decision-making processes.…”
Section: Mateusz Trylinski and Buzz Baummentioning
confidence: 99%
“…Our ability to see is mediated by a family of opsin proteins in the retina. When exposed to light, opsins modulate the flow of ions across neuronal membranes, ultimately activating the optic nerves 1 . In mammals, an opsin called opsin 5 (OPN5) is expressed in an unusual place -in neurons deep in the brain's preoptic area 2 (POA), which has a role in metabolism.…”
mentioning
confidence: 99%